2020
DOI: 10.1055/s-0040-1707254
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Denitrogenative Reactions of Pyridotriazoles

Abstract: Diazo compounds display versatile reactivity and therefore are widely used in organic synthesis. Diazo compounds bearing a 2-pyridyl or a related azine moiety on the diazo carbon exist in the form of fused 1,2,3-triazoles. In this short review, we summarize the recent advances in denitrogenative reactions of [1,2,3]triazolo[1,5-a]pyridines (‘pyridotriazoles’) and related fused 1,2,3-triazoles. Over the past decade, there has been a surge of activity in this field, with novel denitrogenative reactions of pyrido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…41 In 2021 Severin et al reported the functionalization of nitrous oxide for the synthesis of triazolopyridines and triazoloquinolines, 40 which are useful building blocks for heterocycle synthesis. [42][43][44][45][46][47] The reaction was performed in two steps, the first consisting of the lithiation of 2-alkylpyridine and 2-alkylquinoline derivatives, and the second one involving nitrous oxide for its functionalization to triazolopyridine and triazoloquinoline scaffolds (see Scheme 1), to be compared with other synthesis strategies like those with t BuONO 48 or azides. 49 The reaction pathway was hypothesized (see Scheme 2) as an initial nucleophilic attack of the carbanion on nitrous oxide to yield a diazotate, followed by the elimination of LiOH to generate the diazo species and finally cyclization to give the final desired product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 In 2021 Severin et al reported the functionalization of nitrous oxide for the synthesis of triazolopyridines and triazoloquinolines, 40 which are useful building blocks for heterocycle synthesis. [42][43][44][45][46][47] The reaction was performed in two steps, the first consisting of the lithiation of 2-alkylpyridine and 2-alkylquinoline derivatives, and the second one involving nitrous oxide for its functionalization to triazolopyridine and triazoloquinoline scaffolds (see Scheme 1), to be compared with other synthesis strategies like those with t BuONO 48 or azides. 49 The reaction pathway was hypothesized (see Scheme 2) as an initial nucleophilic attack of the carbanion on nitrous oxide to yield a diazotate, followed by the elimination of LiOH to generate the diazo species and finally cyclization to give the final desired product.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021 Severin et al reported the functionalization of nitrous oxide for the synthesis of triazolopyridines and triazoloquinolines, 40 which are useful building blocks for heterocycle synthesis. 42–47 The reaction was performed in two steps, the first consisting of the lithiation of 2-alkylpyridine and 2-alkylquinoline derivatives, and the second one involving nitrous oxide for its functionalization to triazolopyridine and triazoloquinoline scaffolds (see Scheme 1), to be compared with other synthesis strategies like those with t BuONO 48 or azides. 49…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews regarding pyridotriazoles especially their transition metal catalyzed reactions were published [12,17–21] . However, the chemistry of pyridotriazoles contains many special features and deserves more attention.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Several reviews regarding pyridotriazoles especially their transition metal catalyzed reactions were published. [12,[17][18][19][20][21] However, the chemistry of pyridotriazoles contains many special features and deserves more attention. In particular, the advance on the synthesis of these compounds has not been well summarized.…”
Section: Introductionmentioning
confidence: 99%
“…17 One is non-diazo-type sources, such as enynones, cyclopropenes, and pyridotriazoles, which have been thoroughly reviewed. [18][19][20][21] The other is diazo-type carbene sources, which include diazo compounds and hydrazones. Due to space constraints, this review focuses primarily on the latter, specifically the use of N-sulfonylhydrazones as silver carbene precursors.…”
Section: Introductionmentioning
confidence: 99%